2020
DOI: 10.1016/j.psj.2020.04.010
|View full text |Cite
|
Sign up to set email alerts
|

High levels of contact dermatitis and decreased mobility in broiler breeders, but neither have a relationship with floor eggs

Abstract: Contact dermatitis, both on the foot pads and hocks, is a well-known health issue in broilers. Less is known about contact dermatitis in broiler breeders, however, although they have many risk factors for developing leg health problems in common with broilers. This study aimed to describe the prevalence and severity of contact dermatitis during the production cycle in 5 lines of broiler breeders, investigate possible causes of contact dermatitis, and study its relationship with gait, egg production, and floor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Providing aerial perches enables females to avoid unwanted sexual behaviour from the males to a certain extent (Gebhardt‐Henrich et al., 2020 ) and would be feasible in furnished cages. Besides perches, raised slats (van den Oever et al., 2020a ), part‐time separation between the sexes (van Emous, 2010 ), or cover panels can reduce forced copulations and overmating (Leone and Estévez, 2008 ).…”
Section: Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Providing aerial perches enables females to avoid unwanted sexual behaviour from the males to a certain extent (Gebhardt‐Henrich et al., 2020 ) and would be feasible in furnished cages. Besides perches, raised slats (van den Oever et al., 2020a ), part‐time separation between the sexes (van Emous, 2010 ), or cover panels can reduce forced copulations and overmating (Leone and Estévez, 2008 ).…”
Section: Assessmentmentioning
confidence: 99%
“…Studies have reported unhealed navels and enlarged yolk sacs to be the abnormalities most frequently registered during chick quality assessment of both on-farm and hatchery-hatched chicks, but with a higher prevalence in chicks hatched on-farm (van de Ven et al, 2012;Jessen et al, 2021b). For example, Jessen et al (2021b) reported unhealed navels to occur in 8.2% of the chicks hatched on-farm, whereas the prevalence was 5.3% for the hatchery-hatched chicks.…”
Section: Umbilical Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Cellulitis usually develops from initial skin scratches, which allow entry of bacteria into the subcutaneous tissue where they subsequently proliferate and cause infection ( Jeffrey et al, 2004 ; Bernd et al, 2020 ). However, as carcasses with cellulitis in the current study were free from scratches, the development of cellulitis may be attributed to other predisposing factors, i.e., wet irritated skin in combination with stress, genetic factors, nutritional deficiency, population density, litter quality, and breeders’ and hatchery hygiene ( Dziva and Stevens, 2008 ; Allain et al, 2009 ; Kabir, 2009 ; Poulsen et al, 2018 ; Alfifi et al, 2020 ; Iannetti et al, 2020 ; van den Oever et al, 2020 ). A recent investigation of management factors associated with cellulitis reported that measures to reduce stress in broiler flocks reduced the risk of cellulitis ( Bernd et al, 2020 ).…”
Section: Resultsmentioning
confidence: 78%